Interaction between Bacillus spp. and graphene oxide: Impacts on physiological and nutritional modulation for improving sugarcane drought resilience - de Almeida Silva, Marcelo [UNESP]; Luiz Santos, Hariane [UNESP]; de Sousa Ferreira, Lusiane [UNESP]; de Castro Nogueira, Carlos Henrique [UNESP]; Rodrigues Alves Carnietto, Melina [UNESP]; Dos Santos, Karolyne P O [UNESP] (Elsevier, 2025)
The synergistic application of plant growth-promoting bacteria (PGPB) and nanomaterials, such as graphene oxide (GO), represents a promising strategy to mitigate the adverse effects of water deficit in crops, offering new perspectives on agricultural resilience and sustainability. This research aimed to evaluate the inoculation with Bacillus subtilis (strain FMCH002) and Bacillus licheniformis (strain FMCH001), alone or in combination with GO, on drought tolerance in sugarcane through physiological, biochemical, and nutritional responses. A completely randomized 4 × 2 factorial design was used, consisting of four products [control, PGPB, GO, and PGPB + GO] under two water regimes [well-watered (-W; 100 % field capacity - FC) and water deficit (+W; 50 % field capacity)]. The PGPB-GO combination reduced vapor pressure deficit and enhanced net CO2 assimilation, stomatal conductance, intercellular CO2 concentration, and relative water content. Under W, PGPB increased the activities of antioxidant enzymes, including ascorbate peroxidase (EC 1.11.1.11), peroxidase (EC 1.11.1.7), catalase (EC 1.11.1.6), and superoxide dismutase (EC 1.15.1.1), while promoting proline accumulation and reducing H2O2 and malondialdehyde levels. Furthermore, the PGPB-GO combination enhanced the availability and uptake of nitrogen, phosphorus, potassium, and micronutrients in both leaves and roots, resulting in greater dry matter accumulation in leaves, sheaths, and stalks. GO alone also increased stalk biomass and root volume. Overall, our findings demonstrate that combining B. subtilis FMCH002 and B. licheniformis FMCH001 with GO is a viable and effective strategy for alleviating drought stress, improving nutrient acquisition, and enhancing biomass accumulation in sugarcane.